Real-time surveillance of formaldehyde gas levels in sugar carbonation processes through web-enabled MS1100 sensor monitoring - Afifah, Arsa; Wardoyo, Arinto Yudi Ponco; Jatra, Ananta S; A, Renetha Salma Myesha (Journal of Applied Science and Advanced Engineering, 2024)
The refining process of sugar cane juice includes a crucial stage termed carbonation, which is pivotal for achieving pH balance through the utilization of carbon dioxide (). The need for is fulfilled by burning biomass, including rice husks and sugarcane bagasse. However, this process can generate hazardous compounds, notably Formaldehyde (), posing significant health risks. To address elevated Formaldehyde concentration, a monitoring system is implemented, employing an MS1100 sensor for real-time monitoring within the carbonation tank. The data is transmitted to a web-based platform via Robotdyn Uno Wi-Fi R3, with direct data storage on a micro SD card to ensure persistence even during Wi-Fi disruptions. The system confirms the efficacy of monitoring the formaldehyde concentrations both indoors and outdoors, maintaining levels within the safe thresholds. The system demonstrates high accuracy, making it a viable solution for monitoring and regulating Formaldehyde emissions during biomass burning in the sugar industry.